PSIX-19 Effects of ValiMP® supplementation on growth performance, carcass characteristics, and pork quality in growing-finishing pigs - Park, Min Young (J Anim Sci, 2019)
ValiMP(®) is a mixture of phytochemical compounds containing manganese. An experiment was carried out to evaluate the effects of ValiMP(®) on growth performance, carcass characteristics, and pork quality in growing-finishing pigs. The trial was conducted in a 2x3 factorial design with two levels of CP (LP, 15% or HP, 16%), and three types of supplements (Control; 10 ppm ractopamine; or 0.25% ValiMP(®)). Dietary treatments were: LC (Low CP+control), LR (Low CP+ractopamine), LV (Low CP+ValiMP(®)), HC (High CP+control), HR (High CP+ractopamine), HV (High CP+ValiMP(®)). A total of 144 growing pigs at 50 kg initial body weight (BW) were allotted and fed one of the experimental diets for 70 days. But ractopamine in LR and HR treatments was supplemented during the last 35 days. BW and feed intake were measured weekly, and pork quality was determined in longissimus dorsi muscle. All values were statistically analyzed using ANOVA procedure of SAS 9.4 software and differences at P < 0.05 level were considered significantly different. Results showed dietary ractopamine or ValiMP(®) supplementation numerically promoted growth performance compared to control in HP treatments, although the extent was lesser in ValiMP(®) treatment. Ractopamine or ValiMP(®) also improved carcass composition in HP compared to LP. Lean percentage in HR was higher than in LR by 4.3%, and it was greater in HV than in LV by 5.9%, (P < 0.05). These changes occurred at the expense of fat percentage (P < 0.05). Among pork quality criteria, water-holding capacity determined by filter-paper fluid uptake method was significantly lower in HV than those in HC and HR (P < 0.05). Warner-Bratzler shear force, an indicative for meat tenderness, exhibited lower values in HV and HC than that in HR (P < 0.05). Overall, our results suggest ValiMP(®) improves growth performance and carcass composition with lesser extent to ractopamine, and pork quality more than ractopamine. [Image: see text] [Image: see text] [Image: see text]